Mixing effect of anionic and nonionic surfactants on micellization, adsorption and partitioning of nonionic surfactant - Muherei, Mazen Ahmed; Junin, Radzuan (Modern Applied Science, 2008)
Nonionic surfactants are always good candidates for surfactant enhanced aquifer remediation (SEAR), enhanced oil recover (EOR) and insitu/ex-situ soil washing. Their wide application is based on their high solubilization capacities and their low bio-toxicity. However, surfactant loss due to adsorption and/or partitioning on adsorbents impairs their effectiveness to solubilize/mobilize and reduce the oil–water interfacial tension (IFT) which renders contaminant remediation process economically unfeasible. In this research anionic (SDS) and nonionic (TX100) surfactants and their mixtures (1:2, 1:1, 2:1; TX100:SDS mass ratios) were evaluated for their ability to reduce surfactant CMCs, partitioning losses to an organic phase and/or adsorption to shale. Result showed that all mixtures behave similarly and have superior properties than both single surfactants. Partitioning and adsorption of TX100 into organic phase (Sarapar147) and shale were decreased by mixing with anionic surfactant (SDS). The data showed a 40% reduction in surfactant losses due to adsorption to shale and around 60% reduction due to both partitioning and adsorption.